Proses Produksi Musik pada Lagu Tyok Satrio di Studio DS Records - Puput Pramuditya; Arya Putra Hananta (Institut Seni Indonesia Denpasar, 2023)
Purpose: The purpose of this research is to identify and describe the music production process for Tyok Satrio's songs which were performed independently at Studio DS Records by Danurseto Bramana Adhi. Various stages from writing songs to making musical accompaniment are integrated into one unified music production process. According to Sawyer and Golding, music production has 3 (three) general stages, namely: (1) Pre-production which contains all musical concept planning as an efficiency of the recording process; (2) Production, namely the recording process in music production which involves all musicians; (3) Post Production is the last phase which contains the process of editing, balancing, mixing-mastering to present songs ready to be heard. Method: This study uses qualitative methods to discover and understand the various phenomena encountered to then be analyzed carefully. Data collection techniques were carried out by observation, interviews, and documentation. Results and discussion: The results and discussion show that the music production process carried out by Danurseto is carried out using the Sawyer and Golding methods with all departmental roles integrated with each other by the same person. Implication: the music production process for the song Tyok Satrio, which was carried out by Danurseto as producer, A&R, songwriter, arranger, instrumentalist, and sound engineer, can simultaneously achieve work efficiency by way of work mechanisms that are mutually integrated at each stage.